DESIGNING A MICROSOFT EXCEL-BASED COFFEE SALES RECORDING SYSTEM USING INDEX, MATCH, AND SUMIFS FUNCTIONS (Case Study Of PT. DEF) - Risna Anggaini; Syafran Nurrahman; Saskia Nur Ramadhani; Yohana Cesyika Ndaung (PT. Jurnal Center Indonesia Publisher, 2026)
DEF is a company engaged in the sale of coffee, both wholesale and retail. Currently, the sales recording system is still carried out manually, which often leads to problems such as delays in reporting, data entry errors, and difficulties in retrieving historical information. This study aims to improve the efficiency and accuracy of the sales recording system by implementing the INDEX MATCH and SUMIFS functions in Microsoft Excel. The research method used is descriptive qualitative with a case study approach, involving observation, interviews, and documentation of the existing system. The results show that the use of INDEX MATCH and SUMIFS can accelerate the data retrieval process, improve the accuracy of sales reports, and reduce input errors. This study provides a practical solution for small and medium enterprises (SMEs) in implementing an efficient sales recording system without requiring significant investment in ERP software. However, the system still has limitations, such as dependence on Excel files that are vulnerable to damage or unintended changes, and the lack of advanced automation features such as receivables reminders or inter-departmental integration. Therefore, future research is expected to develop a web-based system with a centralized database.